Politics and aesthetics in European baroque and classicist tragedy - Bloemendal, Jan; Smith, Nigel (2016)
"Politics and Aesthetics in European Baroque and Classicist Tragedy is a volume of essays investigating European tragedy in the seventeenth century, comparing Shakespeare, Vondel, Gryphius, Racine and several other vernacular tragedians, together with consideration of neo-Latin dramas by Jesuits and other playwrights. To what extent were similar themes, plots, structures and styles elaborated? How is difference as well as similarity to be accounted for? European drama is beginning to be considered outside of the singular vernacular frameworks in which it has been largely confined (as instanced in the conferences and volumes of essays held in the Universities of Munich and Berlin 2010-12), but up-to-date secondary material is sparse and difficult to obtain. This volume intends to help remedy that deficit by addressing the drama in a full political, religious, legal and social context, and by considering the plays as interventions in those contexts. Contributors are: Christian Biet, Jan Bloemendal, Helmer J. Helmers, Blair Hoxby, Sarah M. Knight, Tatiana Korneeva, Frans-Willem Korsten, Joel B. Lande, Russell J. Leo, Howard B. Norland, Kirill Ospovat, James A. Parente, Jr., Freya Sierhuis, Nienke Tjoelker and Emily Vasiliauskas"–...